2004
DOI: 10.1179/136485904x12386
|View full text |Cite
|
Sign up to set email alerts
|

Responses ofMastomys coucha, that have been infected withBrugia malayiand treated with diethylcarbamazine or albendazole, to re-exposure to infection

Abstract: The responses of Mastomys coucha to re-exposure to infection with homologous infective larvae (L(3)) of Brugia malayi were investigated, after initial infections with the nematode had been treated subcutaneously for 5 days with diethylcarbamazine (DEC; 150 mg citrate/kg. day) or albendazole (ALB; 50 mg/kg. day). The parasite burdens, serum concentrations of IgG reacting with a soluble somatic extract of adult B. malayi (BmAS), and cytokine and lymphocyte-proliferative responses to filarial antigen (BmAS) or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Mastomys rodents that were cleared of infection by using albendazole displayed resistance to subsequent infection. However, this might not be due to the chemically abbreviated infection, as the control group, which received only albendazole, was also resistant to infection (61).…”
Section: Brugia Malayimentioning
confidence: 99%
See 1 more Smart Citation
“…Mastomys rodents that were cleared of infection by using albendazole displayed resistance to subsequent infection. However, this might not be due to the chemically abbreviated infection, as the control group, which received only albendazole, was also resistant to infection (61).…”
Section: Brugia Malayimentioning
confidence: 99%
“…Infections have been chemically abbreviated by using either albendazole or diethylcarbamazine (DEC) (61). Abbreviation of infection with DEC does not elicit any significant protection against future infection (61).…”
Section: Brugia Malayimentioning
confidence: 99%
“…The reasons for this are not clear. Our previous study showed that treatment with ALB inhibits the development of new incoming infection while treatment with DEC facilitates it (Khan et al, 2004). These findings suggested that alterations in the specific immunological responses may play an important role in the development of reinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has optimised mouse model of Brugian filariasis Khan et al, 2004), and its chemotherapeutic responses to DEC and IVM match with those reported for humans. Therefore, we successfully applied DEC treatment and reinfection approach to investigate changes in parasite antigens during course of DEC treatment.…”
Section: Introductionmentioning
confidence: 90%
“…Infective third stage larvae (L 3 ) of B. malayi were obtained from laboratory bred female Aedes aegypti fed on microfilaraemic Mastomys coucha as described previously Khan et al, 2004).…”
Section: Infectionmentioning
confidence: 99%